1997
DOI: 10.1088/0022-3727/30/11/014
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the computation of the composition of quenching media in HV circuit breakers after current zero

Abstract: General equations are derived whose solution gives the dependence of species concentrations of a closed gaseous system on time for a given dependence of temperature on time, on the assumption that either the dependence of pressure in on time or the dependence of volume of system on time is given. Some results from solving a previously proposed model are given for the case when is created by the products of dissociation and ionization and the temperature decreases exponentially from 10 000 K to 2500 K. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…As many reactions are reversible, the reverse rate constants (r kz ) are obtained with the assistance of the forward rate constant (r k ) and the relative equilibrium constant (K k ) [10]. With the recommendation of Gurvich et al [11], K k is given by…”
Section: Two-temperature Chemical Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As many reactions are reversible, the reverse rate constants (r kz ) are obtained with the assistance of the forward rate constant (r k ) and the relative equilibrium constant (K k ) [10]. With the recommendation of Gurvich et al [11], K k is given by…”
Section: Two-temperature Chemical Kinetic Modelmentioning
confidence: 99%
“…, NF, NS and 80 reactions, with 76 to be reverse ones. The reactions are obtained from the work of Girard et al [13], Adamec et al [11], Teulet et al [14], Woodall et al [15] and Bartlová et al [10] as shown in table 1.…”
Section: Two-temperature Chemical Kinetic Modelmentioning
confidence: 99%
“…All the necessary reaction rate coefficients, temperature dependences and collision cross sections have been compiled from numerous literature references as well as parametric studies. Differently from the initiatory paper by Brand and Kopainsky [3] and works of Gleizes et al [4] and Adamec and Coufal [5], the temperature calculation and the inclusion of electronimpact processes are the new points presented here. In addition to the chemical kinetics, we have also modelled a time-dependent diffusion rather than linking the chemical kinetics to the ideal gas law.…”
Section: Introductionmentioning
confidence: 94%
“…In works on the kinetics of chemical reactions in HV circuit breakers the definition of the rate of reaction is, for reasons unknown, not given. An exception is our earlier article [23], in which definition (12) is given but all the rate constants have been taken over from Brand and Kopainsky [1], where there is no definition of the rate of reaction. From…”
Section: Rate Constantmentioning
confidence: 99%